2008
DOI: 10.1099/mic.0.2008/021584-0
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of CprK paralogues from Desulfitobacterium hafniense in activating gene expression

Abstract: Gene duplication and horizontal gene transfer play an important role in the evolution of prokaryotic genomes. We have investigated the role of three CprK paralogues from the cAMP receptor protein-fumarate and nitrate reduction regulator (CRP-FNR) family of transcriptional regulators that are encoded in the genome of Desulfitobacterium hafniense DCB-2 and possibly regulate expression of genes involved in the energy-conserving terminal reduction of organohalides (halorespiration). The results from in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
7
18
1
Order By: Relevance
“…This was for the reason that functional screening of rdhA seems to be difficult because functional expression of rdhA genes in E. coli has not been successful [53,54]. On the other hand, the utility of an in vivo transcription assay of the transcriptional regulator CprK in E. coli has been proved [55], indicating that it might be possible to explore genes involved in organohalide respiration using SIGEX transcriptional screening. Contrary to the results of the 16S rRNA gene sequence analysis, which indicated that Desulfuromonadales species predominated in the dehalogenation-positive enrichment cultures, SIGEX suggested the presence of a phylogenetically diverse assortment of clones putatively belong to the Gammaproteobacteria, Deltaproteobacteria, Dehalococcoidetes, Deferribacteres and Methanomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…This was for the reason that functional screening of rdhA seems to be difficult because functional expression of rdhA genes in E. coli has not been successful [53,54]. On the other hand, the utility of an in vivo transcription assay of the transcriptional regulator CprK in E. coli has been proved [55], indicating that it might be possible to explore genes involved in organohalide respiration using SIGEX transcriptional screening. Contrary to the results of the 16S rRNA gene sequence analysis, which indicated that Desulfuromonadales species predominated in the dehalogenation-positive enrichment cultures, SIGEX suggested the presence of a phylogenetically diverse assortment of clones putatively belong to the Gammaproteobacteria, Deltaproteobacteria, Dehalococcoidetes, Deferribacteres and Methanomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…Most of rdh gene clusters are also associated with one rdhK subunit in various orientations. The rdhK-encoded proteins clearly belong to the large family of CRP/Fnr regulatory proteins from which CprK members of Desulfitobacterium dehalogenans and Desulfitobacterium hafniense DCB-2 were extensively studied and represent the paradigmatic DNA-binding regulatory protein for the respective chlorophenol reductive dehalogenase (cpr) operons [48][49][50][51][52][53][54][55][56] figure 3). First, a strong correlation could be established between the level of sequence identity (see also electronic supplementary material, table S7) and the genetic organization of the predicted rdh operons.…”
Section: (I) Multiple Reductive Dehalogenase Homologue Gene Clusters mentioning
confidence: 99%
“…PCP was then added at 30 M, whereas 2,4,6-TCP was added at 0. 125,5, 25, and 50 M and 3,3,6, 30, and 60 M (final concentration). The cultures were incubated at 30°C for 12 h. For the temperature experiment, the bottles were incubated for 3 h at 22, 30, or 37°C prior to addition of 3,5-DCP at 60 M. The bottles were further incubated for 12 h at these temperatures.…”
mentioning
confidence: 99%